2015
DOI: 10.1055/s-0035-1554622
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of Endothelial Cell Function Induced by Hemoglobin A1c and the Potential Mechanisms

Abstract: These findings provide direct evidence that HbA(1c) is involved in the development and progression of the cardiovascular complications of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…After 24 h in culture, PHb did not influence the migratory capacity of C2C12 cells. Thus, we decided to prolong the assay for an additional 24 h. After 48 h, PHb slightly inhibited the migration of these cells, which is in accordance with a previous study that showed that HbA1c, glycated hemoglobin isolated from patients with type 2 diabetes, reduced the migration of HUVEC cells in a dose-and time-dependent manner [48]. Also, it was reported that two peptides derived from BHb blocked about 50% and 30% wound closure in a scratch assay of the MIAPaCa-2 cell line when compared to the control group after treating for 72 h [37].…”
Section: Discussionsupporting
confidence: 84%
“…After 24 h in culture, PHb did not influence the migratory capacity of C2C12 cells. Thus, we decided to prolong the assay for an additional 24 h. After 48 h, PHb slightly inhibited the migration of these cells, which is in accordance with a previous study that showed that HbA1c, glycated hemoglobin isolated from patients with type 2 diabetes, reduced the migration of HUVEC cells in a dose-and time-dependent manner [48]. Also, it was reported that two peptides derived from BHb blocked about 50% and 30% wound closure in a scratch assay of the MIAPaCa-2 cell line when compared to the control group after treating for 72 h [37].…”
Section: Discussionsupporting
confidence: 84%
“…Even though extracellular hemoglobin can be a part of the PB-MSC microenvironment, data in the literature regarding its influence on mesenchymal cells' migratory capacity are scarce. Bo et al [41] demonstrated that human glycated hemoglobin (HbA1c) inhibited the migration of HUVEC cells in a dose-and time-dependent manner [41]. Likewise, the peptides derived from bovine hemoglobin had the same effect on the MIAPaCa-2 cell line's migratory capacity [42].…”
Section: Discussionmentioning
confidence: 99%
“…For example, one of the pathways presented in Figure 2 is HbA1c→NOS3→NAFLD. It has been shown that increased concentrations of HbA1c are capable of significantly down-regulating the expression of NOS3 [27]; resultant deficiency of NOS3 is a known contributor to NAFLD [28]. Another example is the HbA1c→ IL10→NAFLD pathway.…”
Section: Discussionmentioning
confidence: 99%